Implementation of Visual and Performing Arts (VPA) in ELT Through Kampus Mengajar Program at Secondary School in Southwest Papua - Hasyim, Ruslan; Hasanudin, Hasanudin; Wael, Ahmad; Saputra, Dian; Hardianti, Rinda; Uluelang, Kris; Srianah Amir, Hasbiyah; Mohammad Sata, Mohammad Rafi'i (ITScience (Information Technology and Science), 2024)
This research discusses the implementation of Visual and Performing Arts (VPA) in the Campus Teaching Program at SMP Negeri 1 Kota Sorong, Southwest Papua. The research methodology employed is descriptive analysis, involving eighth-grade students as research subjects. Various work programs were implemented, such as Canva-based digital learning,